1977
DOI: 10.1111/j.1476-5381.1977.tb06990.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti‐thyroid Agents, Methimazole and Propylthiouracil, on Brain Noradrenaline Content

Abstract: 1Methimazole (1-methyl-2-mercaptoimidazole, MMI) and propylthiouracil (6-propyl-2-thiouracil, PTU) which are used in the therapy of hyperthyroidism were found to reduce brain noradrenaline (NA) content. Endogenous NA levels in rat brain were reduced from 1 to 6 h after intraperitoneal injection of MMI by doses in excess of 25 mg/kg and by PTU at a dose of 50 mg/kg. However, endogenous NA in the rat heart was only slightly reduced after 50 mg/kg of MMI, and was not affected by PTU (50 mg/kg). 2 Both MMI and PTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The capability of methimazole to attenuate the direct inflammatory response suggested an anti-inflammatory role. As mentioned above, methimazole has been found to inhibit the glial cell function in a diabetic mouse model [14]. Our results were consistent with these previous results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The capability of methimazole to attenuate the direct inflammatory response suggested an anti-inflammatory role. As mentioned above, methimazole has been found to inhibit the glial cell function in a diabetic mouse model [14]. Our results were consistent with these previous results.…”
Section: Discussionsupporting
confidence: 94%
“…Methimazole is an antithyroid compound that has been broadly used in the treatment of hyperthyroidism and Graves disease via preventing the production of the level of thyroid hormones from the thyroid gland. Interestingly, methimazole was also found to have significant impact on CNS by influencing the levels of varieties of neurotransmitters [14]. A previous study also suggested that methimazole could regulate the opioid receptor expression in the brain [15].…”
Section: Introductionmentioning
confidence: 98%
“…Increases in adrenal, cardiac, and brain DA and decreases in brain NE following the administration of DBH inhibitors are well documented (17)(18)(19). Further, DA increases following the administration of DBH inhibitors have been related to the ability of such inhibitors to prevent the conversion of 23H-DA to 3H-Ne (17), indicating that tissue DA increases and NE decreases were at least in part due to the ability of the inhibitor to produce in vivo DBH inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…I t has a1 so been reported (Hashizume and Yamaki , 1977) of Lindsay e t a1 . (1 966, 1968a), Lindsay -(-1969), and Doniach ( 7 970, 1 974) .…”
Section: Thyroid Hormone Actionmentioning
confidence: 88%